Characterization of Amino Acid Composition, Nutritional Value, and Taste of Fruits from Different Actinidia arguta Resources - Yanli He; Hongyan Qin; Jinli Wen; Lin Wang; Weiyu Cao; Shutian Fan; Wenpeng Lu; Jiaqi Li; Changyu Li (Journal of Food Quality)
The nutritional value and flavor and texture characteristics of fruits from different Actinidia argute resources were scientifically evaluated and compared. Using 35 A. arguta fruits as materials, the amino acid composition and content were determined by an automatic amino acid analyzer, and differentiation analysis, amino acid nutritional value evaluation, TAV flavor analysis, correlation analysis, PCA comprehensive evaluation, and cluster analysis were conducted to clarify the diversity of A. arguta resources in terms of amino acid content, composition, and flavor characteristics. Analysis of differential results showed that the A. arguta resource fruits contained 17 amino acids with a total amino acid content of 384.20∼2590.56 mg/100 g. The results of the nutritional value evaluation showed that the Leu of the fruits of the A. arguta resources all conformed to the ideal model proposed by FAO/WHO, and the Leu content of all the resources exceeded the human body’s needs, and it was also found that the first limiting amino acid of the Actinidia argute resources was Ile and the second limiting amino acid was Lys. TAV of the flavor-presenting amino acids was calculated to evaluate the flavor-presenting taste characteristics, and the amino acids that influenced the flavor of A. arguta fruit were Glu and Cys. PCA showed that the 2 principal components could better reflect the comprehensive information of amino acids in A. arguta, and the cumulative variance contribution rate was 87.88%, which could represent the main trend of amino acids in A. arguta. A comprehensive amino acid evaluation model was established, and the composite scores indicated that the top 5 excellent resources were S4, S10, S18, S25, and S30. Hierarchical cluster analysis classified the 35 A. arguta resources into 4 categories, which better reflected the differences in amino acid content and composition, nutritional value, and taste characteristics among A. arguta fruits from different collection sites.